Investigation of gene effects and epistatic interactions between Akt1 and neuregulin 1 in the regulation of behavioral phenotypes and social functions in genetic mouse models of schizophrenia - Huang, Ching-Hsun; Pei, Ju-Chun; Luo, Da-Zhong; Chen, Ching; Chen, Yi-Wen; Lai, Wen-Sung (Frontiers in Behavioral Neuroscience, 2015)
Accumulating evidence from human genetic studies has suggested several functional candidate genes that might contribute to susceptibility to schizophrenia, including AKT1 and neuregulin 1 (NRG1). Recent findings also revealed that NRG1 stimulates the PI3-kinase/AKT signaling pathway, which might be involved in the functional outcomes of some schizophrenic patients. The aim of this study was to evaluate the effect of Akt1-deficiency and Nrg1-deficiency alone or in combination in the regulation of behavioral phenotypes, cognition, and social functions using genetically modified mice as a model. Male Akt1+/-, Nrg1+/-, and double mutant mice were bred and compared with their wild-type littermate controls. In experiment 1, general physical examination revealed that all mutant mice displayed a normal profile of body weight during development and a normal brain activity with microPET scan. In experiment 2, no significant genotypic differences were found in our basic behavioral phenotyping, including locomotion, anxiety-like behavior, and sensorimotor gating. However, both Nrg1+/- and double mutant mice exhibited impaired episodic-like memory. Double mutant mice also had impaired sociability. In experiment 3, a synergistic epistasis between Akt1 and Nrg1 was further confirmed in double mutant mice in that they had impaired social interaction compared to the other 3 groups, especially encountering with a novel male or an ovariectomized female. Double mutant and Nrg1+/- mice also emitted fewer female urine-induced ultrasonic vocalization calls. Collectively, our results indicate that double deficiency of Akt1 and Nrg1 can result in the impairment of social cognitive functions, which might be pertinent to the pathogenesis of schizophrenia-related social cognition.